Titanium alloy femoral condyle prosthesis containing bionic porous thin layer and preparation method thereof, and artificial knee joint
By designing bionic porous titanium alloy layer and hard carbon-based film on artificial knee prosthesis, the problem of difficulty in bone tissue growth is solved, the growth and fixation of bone tissue is achieved, and the wear resistance and treatment of the prosthesis are improved. Effect.
Patent Information
- Application Number
- CN202311687425.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-11
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2043-12-11
AI Technical Summary
The existing non-cement fixation artificial knee prosthesis is difficult to achieve bone tissue growth, resulting in poor medium- and long-term fixation effects and the inability to form a stable three-dimensional bone tissue/prosthesis network connection.
A titanium alloy femoral condylar prosthesis containing a bionic porous thin layer was designed. The porosity of the bionic porous titanium alloy layer is 55-80%, and the pore size is 300-650μm. The titanium alloy femoral condylar matrix and porous layer are connected by sintering, and the Hard carbon-based films to improve wear resistance.
The growth and biological fixation of bone tissue are achieved, the interface binding strength is improved, the adverse reactions after surgery are reduced, the bone tissue growth process is enhanced, and the hard carbon-based film is improved wear resistance.
Smart Images

Figure CN117653423B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of medical devices, and in particular to a titanium alloy femoral condyle prosthesis containing a bionic porous thin layer, a preparation method thereof, and an artificial knee joint. Background Art
[0002] Artificial knee replacement can effectively eliminate late-stage knee pain, restore knee function, and improve patients' quality of life. It has become the most effective method for treating end-stage knee diseases caused by various reasons.
[0003] In knee replacement surgery, the fixation methods of artificial knee joints are mainly divided into two categories: bone cement fixation and non-bone cement fixation. The most widely used bone cement fixation prosthesis is currently the bone cement fixation prosthesis, which is fixed in the bone cement by filling bone cement between the installed prosthesis and the bone bed. However, bone cement fixation has bone cement fatigue, which makes bone cement not ideal in maintaining the long-term stability of artificial joints. Non-bone cement fixation prostheses, such as various microporous or hydroxyapatite (HA) coated prostheses, are a fixation method that achieves bone growth and biological closure through the porous surface of the artificial joint in close contact with the bone. Studies have shown that the pore size suitable for bone growth should be 150-700μm. When the pore size is less than 100μm, bone tissue cannot grow into the hole. Existing products associated with non-bone cement fixation prostheses are difficult to achieve effective bone tissue growth and form a stable three-dimensional bone tissue / prosthesis network connection, so the mid- and long-term fixation effect has not improved. Summary of the invention
[0004] The purpose of the present invention is to provide a titanium alloy femoral condyle prosthesis containing a bionic porous thin layer, a preparation method thereof, and an artificial knee joint. The present invention can achieve bone tissue ingrowth between the femoral condyle prosthesis and the bone bed, thereby achieving a good biological fixation effect.
[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0006] The present invention provides a titanium alloy femoral condyle prosthesis, comprising a titanium alloy femoral condyle matrix and a bionic porous titanium alloy layer attached to the inner surface of the titanium alloy femoral condyle matrix; the porosity of the bionic porous titanium alloy layer is 55-80%, and the pore size is 300-650 μm; the pores of the bionic porous titanium alloy layer are a three-dimensional through structure.
[0007] Preferably, it also includes a hard carbon-based film attached to the outer surface of the titanium alloy femoral condyle substrate.
[0008] Preferably, the hard carbon-based film has a thickness of 0.8 to 2.0 μm and a hardness of 15 to 22 GPa.
[0009] Preferably, the bionic porous titanium alloy layer has a thickness of 1 to 4 mm.
[0010] Preferably, the titanium alloy femoral condyle matrix and the bionic porous titanium alloy layer are metallurgically connected by sintering.
[0011] The present invention provides a method for preparing the titanium alloy femoral condyle prosthesis described in the above scheme, comprising the following steps:
[0012] The raw materials for preparing the bionic porous titanium alloy layer are mixed to obtain a titanium alloy slurry; the raw materials for preparing the bionic porous titanium alloy layer include, by mass percentage, 0.5-1% hydroxypropyl methylcellulose, 1-2% agar, 1-3% polyethylene glycol trimethyl nonyl ether, 45-65% first titanium alloy powder and the balance water;
[0013] The titanium alloy slurry is injected into a mold, gelled and solidified, and dried to obtain a gel-like porous titanium alloy blank;
[0014] Pre-sintering and degreasing the gel-like porous titanium alloy blank to obtain a pre-sintered bionic porous titanium alloy;
[0015] Processing the pre-sintered bionic porous titanium alloy into a target size to obtain a bionic porous titanium alloy layer;
[0016] Coating polyoxymethylene on the outer surface layer of the bionic porous titanium alloy layer in contact with the femoral condyle matrix to fill the surface pores, thereby obtaining a bionic porous titanium alloy layer with the outer surface pores filled;
[0017] Mixing raw materials for preparing the titanium alloy femoral condyle matrix and granulating them to obtain feed; the raw materials for preparing the titanium alloy femoral condyle matrix include a second titanium alloy powder and a binder;
[0018] The bionic porous titanium alloy layer filled with the outer surface surface is pre-placed in a femoral condyle mold, and then the feed is injected into the femoral condyle mold for injection molding to obtain a femoral condyle prosthesis embryo;
[0019] Debinding the femoral condyle prosthesis embryo to remove the binder in the femoral condyle matrix and the polyoxymethylene filled on the surface of the bionic porous titanium alloy layer, so as to obtain a titanium alloy femoral condyle prosthesis precursor;
[0020] The titanium alloy femoral condyle prosthesis precursor is subjected to vacuum sintering to obtain the titanium alloy femoral condyle prosthesis.
[0021] Preferably, after the vacuum sintering, the method further comprises: depositing a hard carbon-based film on the outer surface of the titanium alloy femoral condyle substrate by magnetron sputtering.
[0022] Preferably, in terms of mass percentage, the binder includes: 55-65% polyoxymethylene, 10-12% polyethylene glycol, 20-25% low-density polyethylene, 1-3% polypropylene, 2-4% paraffin and 1-3% stearic acid; the mass of the binder is 10-15% of the mass of the second titanium alloy powder.
[0023] Preferably, the vacuum sintering temperature is 1200-1300° C., and the holding time is 2.5-3.5 hours.
[0024] The present invention provides an artificial knee joint, comprising the titanium alloy femoral condyle prosthesis described in the above scheme or the titanium alloy femoral condyle prosthesis prepared by the preparation method described in the above scheme.
[0025] The present invention provides a titanium alloy femoral condyle prosthesis, comprising a titanium alloy femoral condyle matrix and a bionic porous titanium alloy layer attached to the inner surface of the titanium alloy femoral condyle matrix; the porosity of the bionic porous titanium alloy layer is 55-80%, and the pore size is 300-650 μm; the pores of the bionic porous titanium alloy layer are a three-dimensional through-hole structure. The pores of the porous titanium alloy on the inner side of the femoral condyle are a three-dimensional through-hole structure, with an opening rate of >99%, a porosity range of 55-80%, and a pore size distribution of 300-650 μm, which meets the requirements of inducing bone tissue growth, is conducive to the adhesion, growth and differentiation of bone cells, and the porous titanium alloy allows bone tissue to grow into the pores, so that biological fixation is formed between the implant and the bone tissue, and the interface bonding strength is improved. The porous structure can be used to realize the drug loading function, reduce postoperative adverse reactions, improve the treatment effect, and accelerate the growth process of bone tissue.
[0026] In addition, titanium alloy has good biocompatibility, which reduces the adverse reactions of femoral condyle prosthesis in the human body.
[0027] Furthermore, the porous titanium alloy inside the femoral condyle prosthesis and the titanium alloy femoral condyle matrix are metallurgically bonded to have high bonding strength.
[0028] Furthermore, the present invention also has a hard carbon-based film attached to the outer layer of the femoral condyle base, which has good wear resistance, and the carbon material itself has a stable structure and good biocompatibility. The friction coefficient between the carbon-based hard film on the outer side of the femoral condyle and the polyethylene material can be as low as 0.03-0.04, which greatly reduces the wear of the polymer polyethylene gasket.
[0029] The present invention also provides a method for preparing the titanium alloy femoral condyle prosthesis described in the above scheme, which can control the porosity, average pore size, and pore size distribution of the bionic porous titanium alloy layer by controlling the content of the first titanium alloy powder, the stirring speed and time when preparing the gel and slurry, and ultimately obtain a bionic porous structure that has a good match with the elastic modulus and mechanical properties of human bones. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 It is a schematic diagram of the structure of the artificial knee joint of the present invention, wherein 1-titanium alloy femoral condyle base, 2-bionic porous titanium alloy layer, 3-hard carbon-based film, 4-gasket, 5-titanium alloy tibial tray;
[0031] Figure 2 This is a SEM image of the bionic porous titanium alloy layer prepared in Example 1;
[0032] Figure 3 This is a diagram of bone tissue growth in porous titanium alloy cylindrical implants. DETAILED DESCRIPTION
[0033] The present invention provides a titanium alloy femoral condyle prosthesis, comprising a titanium alloy femoral condyle matrix and a bionic porous titanium alloy layer attached to the inner surface of the titanium alloy femoral condyle matrix; the porosity of the bionic porous titanium alloy layer is 55-80%, and the pore size is 300-650 μm; the pores of the bionic porous titanium alloy layer are a three-dimensional through structure.
[0034] In the present invention, the titanium alloy in the titanium alloy femoral condyle matrix and the bionic porous titanium alloy layer is preferably Ti6Al4V, Ti6Al7Nb, Ti5Al3Mo4Zr, Ti5Al2.5Fe, Ti40Ta, Ti15Mo3Nb, Ti12Mo6Zr2Fe, Ti35Nb7Zr5Ta, Ti15Mo, Ti12Mo5Zr3Al, Ti8Fe8Ta or Ti8Fe8Ta4Zr. Metal titanium alloy has good biocompatibility and can reduce adverse reactions of femoral condyle prosthesis in the human body.
[0035] In the present invention, the porosity of the bionic porous titanium alloy layer is preferably 60-75%, more preferably 65-70%; the pore size of the bionic porous titanium alloy layer is preferably 350-600 μm, more preferably 400-550 μm. In the present invention, the thickness of the bionic porous titanium alloy layer is preferably 1.5-3.5 mm, more preferably 2-3 mm. In the present invention, the pores of the bionic porous titanium alloy layer are three-dimensional through structures. The pore structure of the bionic porous titanium alloy layer of the present invention is three-dimensionally through, and its porosity and pore size meet the requirements of inducing bone tissue growth, which is conducive to the adhesion, growth and differentiation of bone cells. At the same time, the porous titanium alloy allows bone tissue to grow into the pores, so that biological fixation is formed between the implant and the bone tissue, and the interface bonding strength is improved. The porous structure can be used to realize the drug loading function, reduce postoperative adverse reactions, improve the treatment effect, and accelerate the growth process of bone tissue.
[0036] In the present invention, the titanium alloy femoral condyle matrix and the bionic porous titanium alloy layer are preferably connected metallurgically by sintering. The present invention adopts metallurgical connection to improve the bonding strength between the femoral condyle matrix and the bionic porous titanium alloy layer.
[0037] In the present invention, the titanium alloy femoral condyle prosthesis preferably also includes a hard carbon-based film attached to the outer surface of the titanium alloy femoral condyle substrate. In the present invention, the thickness of the hard carbon-based film is preferably 0.8-2.0 μm, more preferably 1.0-1.8 μm; the hardness is preferably 15-22 GPa, more preferably 17-20 GPa. The present invention attaches a hard carbon-based film to the outer layer of the femoral condyle substrate, which can improve the wear resistance of the femoral condyle prosthesis, and the carbon material itself has a stable structure and good biocompatibility. By setting a hard carbon-based film, the friction coefficient between the hard carbon-based film on the outside of the femoral condyle and the polyethylene material can be as low as 0.03-0.04, which greatly reduces the wear of the polymer polyethylene gasket.
[0038] The present invention does not make special requirements on the specific composition and structure of the hard carbon-based film. Any carbon-based film that meets the above hardness requirements is known in the art. In an embodiment of the present invention, the hard carbon-based film is specifically a hard carbon-based film disclosed in application number 2023114350300; the hard carbon-based film includes a titanium carbide bottom layer, a titanium carbide-carbon transition layer, a carbon-titanium carbide multilayer and an amorphous carbon top layer stacked in sequence; the titanium carbide bottom layer is in contact with the titanium alloy femoral condyle matrix; the titanium carbide-carbon transition layer is composed of carbon and titanium carbide; the carbon-titanium carbide multilayer is composed of alternating carbon layers and titanium carbide layers. The thickness of the titanium carbide bottom layer is preferably 100 to 200 nm, the thickness of the titanium carbide-carbon transition layer is preferably 100 to 200 nm, and the thickness of the amorphous carbon top layer is preferably 50 to 100 nm. Taking the total thickness of adjacent carbon layers and titanium carbide layers as a modulation period, the modulation period of the carbon-titanium carbide multilayer is preferably 5 to 10 nm; the total thickness of the carbon-titanium carbide multilayer is preferably 550 to 1500 nm. The above structural design enables the overall hard carbon-based film to have both high strength (wear resistance) and low friction coefficient (friction reduction), and good bonding with the titanium alloy femoral condyle matrix.
[0039] The present invention adopts the hard carbon-based film of the above structure. According to the ASTM F1160-14 standard, when the test bar fails in static bending, the film of the coated titanium alloy test bar is not cracked or peeled off after 10 million cycles under the corresponding bending stress of 582MPa.
[0040] The present invention provides a method for preparing the titanium alloy femoral condyle prosthesis described in the above scheme, comprising the following steps:
[0041] The raw materials for preparing the bionic porous titanium alloy layer are mixed to obtain a titanium alloy slurry; the raw materials for preparing the bionic porous titanium alloy layer include, by mass percentage, 0.5-1% hydroxypropyl methylcellulose, 1-2% agar, 1-3% polyethylene glycol trimethyl nonyl ether, 45-65% first titanium alloy powder and the balance water;
[0042] The titanium alloy slurry is injected into a mold, gelled and solidified, and dried to obtain a gel-like porous titanium alloy blank;
[0043] Pre-sintering and degreasing the gel-like porous titanium alloy blank to obtain a pre-sintered bionic porous titanium alloy;
[0044] Processing the pre-sintered bionic porous titanium alloy into a target size to obtain a bionic porous titanium alloy layer;
[0045] Coating polyoxymethylene on the outer surface layer of the bionic porous titanium alloy layer in contact with the femoral condyle matrix to fill the surface pores, thereby obtaining a bionic porous titanium alloy layer with the outer surface pores filled;
[0046] Mixing raw materials for preparing the titanium alloy femoral condyle matrix and granulating them to obtain feed; the raw materials for preparing the titanium alloy femoral condyle matrix include a second titanium alloy powder and a binder;
[0047] The bionic porous titanium alloy layer filled with the outer surface surface is pre-placed in a femoral condyle mold, and then the feed is injected into the femoral condyle mold for injection molding to obtain a femoral condyle prosthesis embryo;
[0048] Debinding the femoral condyle prosthesis embryo to remove the binder in the femoral condyle matrix and the polyoxymethylene filled on the surface of the bionic porous titanium alloy layer, so as to obtain a titanium alloy femoral condyle prosthesis precursor;
[0049] The titanium alloy femoral condyle prosthesis precursor is subjected to vacuum sintering to obtain the titanium alloy femoral condyle prosthesis.
[0050] In the present invention, unless otherwise specified, the raw materials used are commercially available products well known in the art.
[0051] The invention mixes raw materials for preparing the bionic porous titanium alloy layer to obtain titanium alloy slurry.
[0052] In the present invention, the raw materials for preparing the bionic porous titanium alloy layer include, by mass percentage: 0.5-1% hydroxypropyl methylcellulose, 1-2% agar, 1-3% polyethylene glycol trimethyl nonyl ether, 45-65% first titanium alloy powder and remainder water; as a preferred scheme, the hydroxypropyl methylcellulose is preferably 0.6-1.0%, the agar is preferably 1.2-1.8%, the polyethylene glycol trimethyl nonyl ether is preferably 1.5-2.5%, and the first titanium alloy powder is preferably 50-60%.
[0053] In the present invention, the role of the hydroxypropyl methylcellulose (HPMC) is to act as a thickener to improve the mechanical strength of the gel-like porous titanium alloy blank and improve the stability of the bubbles. Agar is the core of the gel system and plays a decisive role in the performance of the slurry. Specifically, the content of agar has a huge impact on the viscosity of the slurry. When the concentration of agar is too high, it will increase the viscosity of the slurry, affect the injection molding, and increase the organic content in the blank. During the degreasing process, the possibility of impurities such as carbides or oxides of Ti will increase; when the agar content is too low, the strength of the blank will be reduced, thereby affecting processing and sintering. Agar is soluble in water at a relatively high temperature (about 80 ° C). When cooled, the agarose chain is reorganized into a helical structure, which is stable due to the combination with water molecules, and this effect will lead to an increase in the viscosity of the suspension. After further cooling, the final gel structure will be obtained, forming a composite structure composed of a multilayer helical structure. At this stage, a large amount of water is combined to form a gel-like structure. Since the green body formed by the agar gel system is not strong enough and is easily damaged during demoulding, degreasing and other processes, HPMC is introduced as a thickener to improve the mechanical strength of the green body. Polyethylene glycol trimethyl nonyl ether (Tergitol) is used as a foaming agent. In the present invention, the particle size of the first titanium alloy powder is preferably 30 to 60 μm.
[0054] In the present invention, the mixing preferably includes: first mixing water, agar and hydroxypropyl methylcellulose to obtain a premixed liquid; adding titanium alloy powder and polyethylene glycol trimethyl nonyl ether to the premixed liquid for second mixing to obtain titanium alloy slurry. In the present invention, the temperature of the first mixing is preferably 60 to 90°C, and the first mixing is preferably carried out under stirring conditions. The present invention has no special requirements for the time of the first mixing, as long as it can ensure the formation of a light yellow, clear and transparent premixed liquid. In the present invention, the second mixing is preferably carried out at 60 to 90°C and under stirring conditions, and the stirring speed is preferably 300 to 400 r / min, more preferably 320 to 380 r / min; the stirring time is preferably 20 to 30 min, more preferably 22 to 28 min.
[0055] After obtaining the titanium alloy slurry, the present invention injects the titanium alloy slurry into a mold, performs gel curing, and dries to obtain a gel-like porous titanium alloy blank.
[0056] In the present invention, the material of the mold is preferably polymethyl methacrylate (PMMA). In the present invention, the temperatures for curing and drying the gel are independently preferably 0 to 10°C, more preferably 2 to 8°C, and further preferably 4 to 6°C.
[0057] After obtaining the gel-like porous titanium alloy blank, the present invention pre-sinters and degreases the gel-like porous titanium alloy blank to obtain a pre-sintered bionic porous titanium alloy.
[0058] In the present invention, the temperature of the pre-sintering degreasing is preferably 600-800°C, more preferably 650-750°C; the holding time is preferably 2-4h, more preferably 2.5-3.5h; the rate of heating to the temperature of the pre-sintering degreasing is preferably 150°C / h. In the present invention, the pre-sintering degreasing is preferably carried out under the protection of argon gas, the argon gas is preferably high-purity argon gas, and the flow rate of the argon gas is preferably 400-600sccm. In the pre-sintering degreasing of the present invention, all other components except the titanium alloy are removed to form a porous structure.
[0059] After obtaining the pre-sintered bionic porous titanium alloy, the present invention processes the pre-sintered bionic porous titanium alloy into a target size to obtain a bionic porous titanium alloy layer. The present invention preferably uses mechanical processing; the present invention does not make special requirements on the processing process.
[0060] After obtaining the bionic porous titanium alloy layer, the present invention coats polyoxymethylene on the outer surface layer of the bionic porous titanium alloy layer in contact with the femoral condyle matrix to fill the surface pores, thereby obtaining a bionic porous titanium alloy layer with the outer surface pores filled;
[0061] The present invention has no special requirements for the injection conditions of the polyoxymethylene, as long as the pores in the biomimetic porous titanium alloy layer can be fully filled. The present invention can prevent titanium alloy powder from entering the pores of the biomimetic porous titanium alloy layer during subsequent injection molding by filling polyoxymethylene.
[0062] The invention mixes raw materials for preparing the titanium alloy femoral condyle matrix, performs granulation, and obtains feed material.
[0063] In the present invention, the raw materials for preparing the titanium alloy femoral condyle matrix include a second titanium alloy powder and a binder; in terms of mass percentage, the binder preferably includes: polyoxymethylene (POM) 55-65%, polyethylene glycol (PEG) 10-12%, low-density polyethylene (LDPE) 20-25%, polypropylene (PP) 1-3%, paraffin (PW) 2-4% and stearic acid (SA) 1-3%; as a more preferred solution, the polyoxymethylene is preferably 57-62%; the polyethylene glycol is more preferably 10.5-11.5%; the low-density polyethylene is more preferably 22-24%; the polypropylene is more preferably 1.5-2.5%; the paraffin is more preferably 2.5-3.5%; the stearic acid is more preferably 1.5-2.5%. In the present invention, the mass of the binder is preferably 10-15% of the mass of the second titanium alloy powder, more preferably 11-14%, and further preferably 12-13%. In the present invention, the particle size of the second titanium alloy powder is preferably 30 to 60 μm.
[0064] The present invention has no special requirements for the mixing and granulation process, and the mixing and granulation methods well known in the art can be used. In the embodiment of the present invention, the second titanium alloy powder and the binder are placed in a mixing and granulating machine, heated, mixed, and granulated to prepare the feed; the stirring rate of the internal mixer is preferably 800-1200r / min, the heating temperature is preferably 100-200°C, and the mixing time is preferably 0.5-2h.
[0065] After obtaining the feed material, the present invention pre-places the bionic porous titanium alloy layer filled with the outer surface surface into a femoral condyle mold, and then injects the feed material into the femoral condyle mold for injection molding to obtain a femoral condyle prosthesis embryo.
[0066] The present invention preferably designs the femoral condyle mold and pouring system used for injection molding according to the structural characteristics of the titanium alloy femoral condyle prosthesis product and the shrinkage rate of the material; the position of placing the bionic porous titanium alloy layer also needs to be considered during the structural design.
[0067] In the present invention, the injection temperature of the injection molding is preferably 140-180°C, more preferably 150-170°C; the injection molding pressure is preferably 80-120MPa, more preferably 90-100MPa; the holding time is preferably 30-45 seconds, more preferably 35-40 seconds.
[0068] After obtaining the femoral condyle prosthesis embryo, the present invention performs binder removal on the femoral condyle prosthesis embryo to remove the binder in the femoral condyle matrix and the polyoxymethylene filled on the surface of the bionic porous titanium alloy layer to obtain a titanium alloy femoral condyle prosthesis precursor.
[0069] In the present invention, the debinding is preferably carried out in a debinding furnace containing an oxalic acid medium; the present invention uses oxalic acid to remove polyoxymethylene. The present invention has no special requirements for the specific amount of the oxalic acid, as long as the polyoxymethylene can be removed. In an embodiment of the present invention, the amount of oxalic acid is specifically 8.0g / min. The debinding temperature is preferably 250-500°C, more preferably 300-450°C, and further preferably 350-400°C; the debinding time is preferably 5-10h, more preferably 6-8h.
[0070] The present invention removes the binder in the femoral condyle matrix and the polyoxymethylene filled on the surface of the bionic porous titanium alloy layer during the debinding process, thereby obtaining the titanium alloy femoral condyle matrix and the bionic porous titanium alloy layer of the target structure.
[0071] After obtaining the titanium alloy femoral condyle prosthesis precursor, the present invention performs vacuum sintering on the titanium alloy femoral condyle prosthesis precursor to obtain the titanium alloy femoral condyle prosthesis.
[0072] In the present invention, the vacuum degree of the vacuum sintering is preferably 3×10 -3 Pa; the temperature of the vacuum sintering is preferably 1200-1300°C, more preferably 1220-1280°C, and further preferably 1240-1260°C; the holding time of the vacuum sintering is preferably 2.5-3.5h, and more preferably 3h.
[0073] The present invention metallurgically combines the titanium alloy femoral condyle matrix and the bionic porous titanium alloy layer on its inner surface, and the combination strength is high.
[0074] In the present invention, after vacuum sintering is completed, the present invention preferably further comprises depositing a hard carbon-based film on the outer surface of the titanium alloy femoral condyle substrate by magnetron sputtering. The present invention does not make special requirements on the conditions of the magnetron sputtering. Hard carbon-based films of different compositions are suitable for different magnetron sputtering conditions. The present invention selects appropriate magnetron sputtering conditions according to the composition of the hard carbon-based film.
[0075] In the present invention, when the hard carbon-based film is the hard carbon-based film disclosed in application number 2023114350300, the magnetron sputtering is: using magnetron sputtering to sequentially deposit a titanium carbide bottom layer, a titanium carbide-carbon transition layer, a carbon-titanium carbide multilayer and an amorphous carbon top layer on the surface of the titanium alloy femoral condyle substrate.
[0076] In the present invention, the magnetron sputtering is preferably closed-field unbalanced magnetron sputtering.
[0077] The present invention preferably places a titanium alloy femoral condyle substrate with a bionic porous titanium alloy layer attached on a rotating worktable, and places a graphite target, a titanium carbide target, a graphite target and a titanium carbide target at 90° on the periphery of the rotating worktable (that is, the angle between any adjacent targets of the four targets is 90°), pre-evacuates the cavity, introduces argon gas, performs pre-sputtering, and then starts to deposit the titanium carbide bottom layer.
[0078] In the present invention, the pre-sputtering time is preferably 30 minutes, and the bias voltage is preferably -500 V. The present invention removes oxide impurities on the surface of the titanium alloy femoral condyle matrix by pre-sputtering.
[0079] In the present invention, the deposition conditions of the titanium carbide bottom layer preferably include: the titanium carbide target current is 2.5 to 4A, more preferably 2.5 to 3.5A; the argon gas flow rate is 40 to 45 sccm, more preferably 42 to 44 sccm; the bias voltage is preferably -100 to -150V, more preferably -110 to -140V, and further preferably -120 to -130V; the deposition time is 10 to 15min. In the present invention, when depositing the titanium carbide bottom layer, the workbench does not rotate, and the two titanium carbide targets work simultaneously.
[0080] After forming the titanium carbide bottom layer, the present invention deposits a titanium carbide-carbon transition layer on the surface of the titanium carbide bottom layer. In the present invention, the deposition conditions of the titanium carbide-carbon transition layer preferably include: the titanium carbide target current is 2 to 3A, more preferably 2.2 to 2.8A, and further preferably 2.4 to 2.6A; the graphite target current gradually increases from 0.5A to 2.5A; the bias voltage is -100 to -200V, more preferably -120 to -180V, and further preferably -140 to -160V; the argon gas flow rate is preferably 20 to 30sccm, more preferably 22 to 28sccm, and further preferably 24 to 26sccm; the deposition time is preferably 10 to 15min, and further preferably 12 to 13min. In the present invention, when depositing the titanium carbide-carbon transition layer, the workbench does not rotate, and the four targets work simultaneously.
[0081] After the titanium carbide-carbon transition layer is formed, the present invention deposits carbon-titanium carbide multiple layers on the surface of the titanium carbide-carbon transition layer.
[0082] In the present invention, the deposition conditions of the carbon-titanium carbide multilayer preferably include: the titanium carbide target current is 2 to 3A, more preferably 2.2 to 2.8A, and further preferably 2.4 to 2.6A; the graphite target current is 1.5 to 2.5A, more preferably 1.8 to 2.3A, and further preferably 2 to 2.1A; the bias voltage is -100 to -200V, preferably -120 to -180V, and further preferably -140 to -160V; the argon gas flow rate is 20 to 30sccm, more preferably 22 to 28sccm, and further preferably 24 to 26sccm; the deposition time is 1.5 to 4.5h, more preferably 2 to 4h, and further preferably 2.5 to 3.5h. In the present invention, during the deposition of the carbon-titanium carbide multilayer, the rotation speed of the rotary table is preferably 3 to 5rpm, and four targets work simultaneously.
[0083] After forming the carbon-titanium carbide multilayer, the present invention deposits an amorphous carbon top layer on the surface of the carbon-titanium carbide multilayer. In the present invention, the deposition conditions of the amorphous carbon top layer preferably include: the graphite target current is 2.5 to 3.5A, more preferably 2.7 to 3.3A, and further preferably 2.9 to 3.1A; the argon gas flow rate is 40 to 45sccm, and further preferably 42 to 43sccm; the bias voltage is -100 to -150V, more preferably -110 to -140V, and further preferably -120 to -130V; the bias voltage adjustment frequency is 0.5 to 1V / min, more preferably 0.6 to 0.9V / min, and further preferably 0.7 to 0.8V / min; the deposition time is preferably 10 to 15min, more preferably 11 to 14min, and further preferably 12 to 13min. In the present invention, when depositing the amorphous carbon top layer, the workbench does not rotate, and the two graphite targets work simultaneously.
[0084] The present invention provides an artificial knee joint, comprising the titanium alloy femoral condyle prosthesis described in the above scheme or the titanium alloy femoral condyle prosthesis prepared by the preparation method described in the above scheme; preferably also comprising a titanium alloy tibial tray and a gasket; the gasket is preferably a highly cross-linked polyethylene gasket.
[0085] Figure 1 FIG. 1 is a schematic diagram of the structure of the artificial knee joint of the present invention. Figure 1 As shown, 1 is a titanium alloy femoral condyle base; 2 is a bionic porous titanium alloy layer; 3 is a hard carbon-based film; 4 is a gasket; and 5 is a titanium alloy tibial tray.
[0086] The titanium alloy femoral condyle prosthesis containing a bionic porous thin layer, its preparation method, and the artificial knee joint provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the scope of protection of the present invention.
[0087] Example 1
[0088] (1) Dissolve 12 g agar and 7 g hydroxypropyl methylcellulose in 300 g deionized water and stir at 80° C. for 0.5 h to form a premix;
[0089] (2) Take 500 g of Ti6Al4V powder with a particle size of 30-60 μm and 20 g of polyethylene glycol trimethyl nonyl ether Tergitol, add them to the premixed solution in step (1), and stir at a speed of 350 r / min for 25 min.
[0090] (3) The titanium alloy slurry obtained in step (2) is injected into a PMMA mold, and the gel is solidified at 0°C and then dried to obtain a gel-like porous titanium alloy blank.
[0091] (4) The gel-like porous titanium alloy blank is pre-sintered and degreased, and the titanium pre-sintering and degreasing process is carried out at a high-purity argon flow rate of 500 sccm, a pre-sintering and degreasing temperature of 750° C., and a heat preservation time of 3 hours to obtain a pre-sintered bionic porous titanium alloy.
[0092] (5) processing the pre-sintered bionic porous titanium alloy in step (4) into a shape with a thickness of 3 mm according to design requirements;
[0093] (6) A layer of polyoxymethylene is coated on the metallurgical bonding surface of the 3 mm thick porous titanium alloy component processed in step (5), and then the component is loaded into the femoral condyle sintering mold. Then, the titanium alloy feed for injection molding and the femoral condyle injection molding are prepared according to the following steps: Ti6Al4V powder with a particle size of 30 to 60 μm is placed in a mixing and granulating machine, and heated, mixed and granulated to prepare the feed. The preparation process is as follows: the stirring rate is 1000 r / min, the temperature is 150°C, and the mixing time is 1 hour. The binder formula is: polyoxymethylene (POM) 60%, polyethylene glycol (PEG) 12%, low-density polyethylene (LDPE) 22%, polypropylene (PP) 1%, paraffin (PW) 3%, stearic acid (SA) 2%. The mass of the binder is 12% of the mass of the titanium alloy powder. The prepared feed is placed in the injection machine trough, and then heated and injected. Injection process: injection temperature is 160°C, injection pressure is 90MPa, and holding time is 30 seconds.
[0094] (7) The titanium alloy embryos injection molded in step (6) are placed in a debinding furnace containing an oxalic acid medium for debinding at a temperature of 400° C. for 6 hours.
[0095] (8) Place the femoral condyle sample after debinding and sintering in step (7) into a vacuum furnace for sintering. Sintering process: vacuum degree 3×10 -3 Pa, sintering temperature is 1250℃; holding time is 3h, and then cooled to room temperature with the furnace. At the same time, the pre-sintered porous titanium alloy in step (4) is processed into The porous titanium alloy cylindrical implant was sintered under the same conditions according to steps (7) and (8) and used as a sample for bone ingrowth verification.
[0096] (9) After polishing the outer surface of the femoral condyle containing porous titanium alloy prepared in step (8), a 1.2 μm thick hard carbon film is coated on the surface using magnetron sputtering technology to obtain a titanium alloy femoral condyle prosthesis.
[0097] The bionic porous titanium alloy layer prepared in this embodiment has a porosity of 71% and a pore size of 300 to 500 μm (e.g. Figure 2 The elastic modulus is 2.7 GPa and the compressive strength is 68 MPa, both of which are close to the mechanical properties of human bones. The porous titanium alloy cylindrical implant was implanted into the leg bone of a beagle dog. Twelve weeks after surgery, the new bone successfully bridged the bone defect, and the porous titanium alloy was filled with bone tissue (such as Figure 3 shown).
[0098] Example 2
[0099] (1) Dissolve 10 g agar and 5 g hydroxypropyl methylcellulose in 300 g deionized water and stir at 80°C for 0.5 h to form a premix;
[0100] (2) Take 500 g of Ti6Al4V powder with a particle size of 30-60 μm and 15 g of polyethylene glycol trimethyl nonyl ether Tergitol, add them to the premixed solution in step (1), and stir at a speed of 320 r / min for 25 min.
[0101] (3) The titanium alloy slurry obtained in step (2) is injected into a PMMA mold, and the gel is solidified at 4°C and then dried to obtain a gel-like porous titanium alloy blank.
[0102] (4) The gel-like porous titanium alloy blank is pre-sintered and degreased, and the titanium pre-sintering and degreasing process is carried out at a high-purity argon flow rate of 500 sccm, a pre-sintering and degreasing temperature of 750° C., and a heat preservation time of 3 hours to obtain a pre-sintered bionic porous titanium alloy.
[0103] (5) processing the pre-sintered bionic porous titanium alloy in step (4) into a shape with a thickness of 3 mm according to design requirements;
[0104] (6) A layer of polyoxymethylene is coated on the metallurgical bonding surface of the 3 mm thick porous titanium alloy component processed in step (5), and then the component is loaded into the femoral condyle sintering mold. Then, the titanium alloy feed for injection molding and the femoral condyle injection molding are prepared according to the following steps: 30-60 μm Ti6Al4V powder, polyoxymethylene, polyethylene glycol, low-density polyethylene, polypropylene, paraffin wax and stearic acid are placed in a mixing and granulating machine, and the mixture is heated, mixed and granulated to prepare the feed. The preparation process is as follows: the stirring rate is 1000 r / min, the temperature is 150°C, and the mixing time is 1 hour. The binder formula is: polyoxymethylene (POM) 60%, polyethylene glycol (PEG) 12%, low-density polyethylene (LDPE) 22%, polypropylene (PP) 1%, paraffin wax (PW) 3%, and stearic acid (SA) 2%. The mass of the binder is 12% of the mass of the titanium alloy powder. The prepared feed is placed in the injection machine trough, and then heated and injected. Injection process: injection temperature is 160°C, injection pressure is 100MPa, and holding time is 30 seconds.
[0105] (7) The titanium alloy embryos injected in step 6) are placed in a debinding furnace containing an oxalic acid medium for debinding at a temperature of 400° C. for 6 hours.
[0106] (8) Place the femoral condyle sample after debinding and sintering in step (7) into a vacuum furnace for sintering. Sintering process: vacuum degree 3×10 -3 Pa, sintering temperature is 1250℃; holding time is 3h, and then cooled to room temperature with the furnace.
[0107] (9) After polishing the outer surface of the femoral condyle containing porous titanium alloy prepared in step (8), a 1.5 μm thick hard carbon film is coated on the surface using magnetron sputtering technology to obtain a titanium alloy femoral condyle prosthesis.
[0108] The bionic porous titanium alloy layer prepared in this embodiment has a porosity of 58%, a pore size of 300-450 μm, an elastic modulus of 16 GPa, and a compressive strength of 198 MPa, all of which are close to the mechanical properties of human bones.
[0109] Example 3
[0110] (1) Dissolve 15 g agar and 8 g hydroxypropyl methylcellulose in 300 g deionized water and stir at 80° C. for 0.5 h to form a premix;
[0111] (2) Take 500 g of Ti6Al4V powder with a particle size of 30-60 μm and 21 g of polyethylene glycol trimethyl nonyl ether Tergitol, add them to the premixed solution in step (1), and stir at a speed of 380 r / min for 25 min.
[0112] (3) The titanium alloy slurry obtained in step (2) is injected into a PMMA mold, and the gel is solidified at 0°C and then dried to obtain a gel-like porous titanium alloy blank.
[0113] (4) The gel-like porous titanium alloy blank is pre-sintered and degreased, and the titanium pre-sintering and degreasing process is carried out at a high-purity argon flow rate of 500 sccm, a pre-sintering and degreasing temperature of 700° C., and the temperature is kept for 4 hours to obtain a pre-sintered bionic porous titanium alloy.
[0114] (5) processing the pre-sintered bionic porous titanium alloy in step (4) into a shape with a thickness of 2 mm according to design requirements;
[0115] (6) A layer of polyoxymethylene is coated on the metallurgical bonding surface of the 2 mm thick porous titanium alloy component processed in step (5), and then the component is loaded into the femoral condyle sintering mold. Then, the titanium alloy feed for injection molding and the femoral condyle injection molding are prepared according to the following steps: Ti6Al4V powder with a particle size of 30 to 60 μm is placed in a mixing and granulating machine, and heated, mixed and granulated to prepare the feed. The preparation process is as follows: the stirring rate is 1000 r / min, the temperature is 150°C, and the mixing time is 1 hour. The binder formula is: polyoxymethylene (POM) 55%, polyethylene glycol (PEG) 11%, low-density polyethylene (LDPE) 21%, polypropylene (PP) 1%, paraffin (PW) 2.6%, and stearic acid (SA) 1.8%. The mass of the binder is 13% of the mass of the titanium alloy powder. The prepared feed is placed in the injection machine trough, and then heated and injected. Injection process: injection temperature is 160°C, injection pressure is 80MPa, and holding time is 30 seconds.
[0116] (7) The titanium alloy embryos injected in step 6) are placed in a debinding furnace containing an oxalic acid medium for debinding at a temperature of 400° C. for 6 hours.
[0117] (8) Place the femoral condyle sample after debinding and sintering in step (7) into a vacuum furnace for sintering. Sintering process: vacuum degree 3×10 -3 Pa, sintering temperature is 1300℃; holding time is 3h, and then cooled to room temperature with the furnace.
[0118] (9) After polishing the outer surface of the femoral condyle containing porous titanium alloy prepared in step (8), a 1.2 μm thick hard carbon film is coated on the surface using magnetron sputtering technology to obtain a titanium alloy femoral condyle prosthesis.
[0119] The bionic porous titanium alloy layer prepared in this embodiment has a porosity of 78%, a pore size of 350-650 μm, an elastic modulus of 1.1 GPa, and a compressive strength of 38 MPa, all of which are close to the mechanical properties of human bones.
[0120] It can be seen from the above embodiments that the present invention provides a titanium alloy femoral condyle prosthesis and a preparation method thereof, and an artificial knee joint. The present invention can achieve bone tissue ingrowth between the femoral condyle prosthesis and the bone bed, thereby achieving a good biological fixation effect.
[0121] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a titanium alloy femoral condyle prosthesis, the titanium alloy femoral condyle prosthesis comprising a titanium alloy femoral condyle matrix and a bionic porous titanium alloy layer attached to the inner surface of the titanium alloy femoral condyle matrix; the porosity of the bionic porous titanium alloy layer is 55-80%, and the pore size is 300-650 μm; the pores of the bionic porous titanium alloy layer are a three-dimensional through structure; The preparation method of the titanium alloy femoral condyle prosthesis comprises the following steps: Mixing raw materials for preparing the bionic porous titanium alloy layer to obtain a titanium alloy slurry; In terms of mass percentage, the raw materials for preparing the bionic porous titanium alloy layer include: 0.5-1% hydroxypropyl methylcellulose, 1-2% agar, 1-3% polyethylene glycol trimethyl nonyl ether, 45-65% first titanium alloy powder and the balance water; The titanium alloy slurry is injected into a mold, gelled and solidified, and dried to obtain a gel-like porous titanium alloy blank; Pre-sintering and degreasing the gel-like porous titanium alloy blank to obtain a pre-sintered bionic porous titanium alloy; Processing the pre-sintered bionic porous titanium alloy into a target size to obtain a bionic porous titanium alloy layer; Coating polyoxymethylene on the outer surface layer of the bionic porous titanium alloy layer in contact with the femoral condyle matrix to fill the surface pores, thereby obtaining a bionic porous titanium alloy layer with the outer surface pores filled; Mixing raw materials for preparing the titanium alloy femoral condyle matrix and granulating them to obtain feed; the raw materials for preparing the titanium alloy femoral condyle matrix include a second titanium alloy powder and a binder; The bionic porous titanium alloy layer filled with the outer surface surface is pre-placed in a femoral condyle mold, and then the feed is injected into the femoral condyle mold for injection molding to obtain a femoral condyle prosthesis embryo; Debinding the femoral condyle prosthesis embryo to remove the binder in the femoral condyle matrix and the polyoxymethylene filled on the surface of the bionic porous titanium alloy layer, so as to obtain a titanium alloy femoral condyle prosthesis precursor; The titanium alloy femoral condyle prosthesis precursor is subjected to vacuum sintering to obtain the titanium alloy femoral condyle prosthesis.
2. The preparation method according to claim 1, characterized in that: After the vacuum sintering, the method further includes: depositing a hard carbon-based film on the outer surface of the titanium alloy femoral condyle matrix by magnetron sputtering.
3. The preparation method according to claim 1, characterized in that: Calculated in percentage by mass, the binder includes: 55-65% polyoxymethylene, 10-12% polyethylene glycol, 20-25% low-density polyethylene, 1-3% polypropylene, 2-4% paraffin and 1-3% stearic acid; the mass of the binder is 10-15% of the mass of the second titanium alloy powder.
4. The preparation method according to claim 1 or 2, characterized in that: The vacuum sintering temperature is 1200-1300° C., and the heat preservation time is 2.5-3.5 hours.
5. The preparation method according to claim 2, characterized in that: The hard carbon-based film has a thickness of 0.8-2.0 μm and a hardness of 15-22 GPa.
6. The preparation method according to claim 1, characterized in that: The thickness of the bionic porous titanium alloy layer is 1-4 mm.
